Disrupted Coordination of Hypoglossal Motor Control in a Mouse Model of Pediatric Dysphagia in DiGeorge/22q11.2 Deletion Syndrome - Wang, Xin (eNeuro, 2020)
We asked whether the physiological and morphologic properties of hypoglossal motor neurons (CNXII MNs) that innervate protruder or retractor tongue muscles are disrupted in neonatal LgDel mice that carry a heterozygous deletion parallel to that associated with DiGeorge/22q11.2 deletion syndrome (22q11.2DS). Disrupted coordination of tongue movement in LgDel mouse pups may contribute to suckling, feeding, and swallowing (S/F/S) disruptions that parallel pediatric dysphagia in infants and toddlers with 22q11.2DS. Using an in vitro rhythmically active medullary slice preparation, we found spontaneous firing as well as IPSC frequency differed significantly in neonatal LgDel versus wild-type (WT) protruder and retractor CNXII MNs that were identified by retrograde tracing from their target muscles. In response to respiration-related activity, initiation and decay of transiently increased firing in WT protruder MNs is delayed in LgDel, accompanied by altered excitatory/inhibitory (E/I) balance. In addition, LgDel retractor MNs have a transient increase in firing with diminished IPSC frequency that is not seen in WT. There were no significant differences in cell body volume of either XII class in WT and LgDel. Sholl analysis showed the total numbers of dendritic intersections (at 50- and 90-μm radii from the cell soma) were significantly greater for LgDel versus WT retractor MNs. Thus, the physiological, synaptic and cellular properties of distinct classes of CNXII MNs that coordinate tongue movement in neonatal WT mice are altered in LgDel. Such changes could contribute to sub-optimal coordination of S/F/S that underlies pediatric dysphagia in 22q11.2DS.